Strategies in Police Integrity Enhancement: A Comprehensive Literature Review - Agus Ady Wijaya (Deviance Jurnal kriminologi, 2023)
This article aims to explain the significant influence of police integrity on service quality and institutional credibility. It delves into the concept of police integrity and explores various strategies for its implementation. The perspectives of Klokars, Ivković, and Haberfeld are used to gain a comprehensive understanding of this concept. The research methodology used in this study involved a thorough literature review, focusing on relevant journal articles and books related to the subject matter. This article provides an in-depth exploration of various aspects related to police integrity and explains various strategies that can be used to enhance police integrity. By highlighting the vital role of integrity in law enforcement agencies, this article contributes to the development of effective best practices and strategies to enhance police integrity to uphold quality-of-service standards and inspire public trust.